On the Observational Equivalence of Unilateral Delegation Contracts in Duopoly - Luca Lambertini; Flavio Delbono (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
In a Cournot duopoly, if only one firm hires a manager while the other remains entrepreneurial, the Cournot-Stackelberg equilibrium emerges, with the managerial firm as the leader. This happens under at least three different delegation schemes. We illustrate the different meachanisms driving this outcome through the analysis of the map of best replies at the market stage.
Keywords: D43; L13; L21; 330